Is the fluoride/creatinine ratio of a spot urine sample indicative of 24-h urinary fluoride? - Zohouri FV, Swinbank CM, Maguire A, Moynihan PJ. (Blackwell Synergy, 2006)
The main aim of this study was to determine how representative the fluoride/creatinine (F/Cr) ratio of a spot urinary sample is of the fluoride content of a 24-h urine sample in young children aged 12– 36 months.